THE EFFECT OF DIGITAL MARKETING ON CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE AMONG E-COMMERCE USERS IN MEDAN CITY - Ami Natuz Zahara; Henry Aspan; Ari Prabowo; Etty Sri Wahyuni (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the effect of digital marketing on customer loyalty with customer satisfaction as an intervening variable among e-commerce users in Medan City. A quantitative approach was applied using non-probability sampling, specifically purposive sampling. The sample consisted of 130 respondents who are active e-commerce users in Medan City and have made at least three online transactions in the past six months. Data were collected through online questionnaires using a five-point Likert scale and analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS) with SmartPLS 4.0 software. The results show that: (1) digital marketing has a positive and significant effect on customer satisfaction (β = 0.718; p < 0.001); (2) customer satisfaction has a positive and significant effect on customer loyalty (β = 0.524; p < 0.001); (3) digital marketing has a positive and significant effect on customer loyalty (β = 0.289; p < 0.001); and (4) customer satisfaction partially mediates the effect of digital marketing on customer loyalty (β = 0.376; p < 0.001). The implication is that e-commerce actors serving the Medan City market need to optimize the digital marketing dimensions, namely cost, interactive, incentive program, site design, and informative, to build customer satisfaction, which will ultimately foster long-term customer loyalty.